1997
DOI: 10.1089/aid.1997.13.1533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tapering Doses of Oral Prednisone on Viral Load among HIV-Infected Patients with Unexplained Weight Loss

Abstract: In an exploratory study of virologic and immunomodulatory effects of corticosteroid therapy for wasting syndrome, four HIV-infected adults with recent unexplained weight loss were given tapering doses of prednisone over a 2-month period. Serum neopterin and TNF receptor II levels decreased from baseline after 7 days. An antiretroviral effect was observed initially, peaking on days 14-21 (mean change in HIV-1 branched chain DNA assay on day 21 of -0.52 log10; mean change, from baseline to nadir for each individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The effect of treatment with steroids has been discussed controversially. Several studies suggested that at least short term or low-dose treatment by steroids is safe with regard to viral load and CD4 counts for the majority of HIV-1 infected patients (Kilby et al, 1997;McComsey et al, 2001;Montaner et al, 2003;Wallis et al, 2003;Walmsley et al, 1995;Ulmer et al, 2005). Indeed, dexamethasone has been shown to exert a direct inhibitory effect on HIV-1 LTR (Kino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of treatment with steroids has been discussed controversially. Several studies suggested that at least short term or low-dose treatment by steroids is safe with regard to viral load and CD4 counts for the majority of HIV-1 infected patients (Kilby et al, 1997;McComsey et al, 2001;Montaner et al, 2003;Wallis et al, 2003;Walmsley et al, 1995;Ulmer et al, 2005). Indeed, dexamethasone has been shown to exert a direct inhibitory effect on HIV-1 LTR (Kino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV positive patients with wasting disease, a reduction in neopterin is seen 7 days after starting oral prednisolone. 30 In both rheumatoid arthritis and SLE a fall in neopterin occurs when patients show a reduction in disease activity in response to immunosuppressive treatment. 18 20 It is interesting that there was no diVerence in UNC ratios between patients on diVerent doses of prednisolone, nor between those on additional second line immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…The treated patients showed reduced T-cell apoptosis in an ex-vivo assay in which mononuclear cells were stimulated with anti-CD3. A subsequent smaller uncontrolled study [24], in which patients with wasting syndrome were treated with corticosteroids for 2 months, observed similar reductions in viral expression and activation markers (serum neopterin and TNFRII). The authors suggested that the inhibition of T-cell activation and activation-induced apoptosis might account for the beneficial effects on T-cell numbers and HIV expression.…”
Section: Steroids and Hiv Pathogenesismentioning
confidence: 79%